Typology of organic residues attracting flies and their utilization in the agricultural sector in southern Benin - BLOUKOUNON-GOUBALAN, ADIN YETON; SAIDOU, ALIOU; CLOTTEY, VICTOR; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; KENIS, Marc; MENSAH, GUY APOLLINAIRE (My University, 2017)
The use of fly larvae as protein source for poultry and agent of biodegradation of organic substrates such as manure proves to be a promising and innovative technology for resource poor farmers. The study aimed at categorizing the organic substrates regarding their capacity to attract flies and to produce fly larvae, and at discussing their utilization in the agricultural domain in southern Benin. A total of 390 farmers were surveyed from October to November 2015 in the six departments (Atlantique, Ouémé, Plateau, Mono, Couffo and Zou) of southern Benin using an open-ended questionnaire. Most of the farmers had limited knowledge on the use of fly larvae to feed poultry. Some of them were not aware of the role of fly larvae in the degradation of the organic substrates. Three utilizations of these organic substrates were mentioned by the farmers: organic fertilizer, fly larvae production, and food for poultry. Animals’ intestines, carcasses, poultry manure, pig manure were mentioned as animal residues attracting flies and potentially suitable for fly larvae production. Suitable plant residues for fly larvae production included agro-artisanal by-products such as soybean bran, corn bran and sorghum bran; brewery malt, rotten papaya fruits, mango rind and rotten banana fruits. The study suggests that these different types of substrate should be assessed for their suitability in fly larvae production and that the quality of residues obtained from the degradation by the fly larvae should be evaluated in the perspective of soil fertility replenishment.
Keywords: organic residue; fly larvae; organic manure; soil fertility; farmer perception.